2009
DOI: 10.1007/s10295-009-0622-z
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia cenocepacia: a new biocatalyst for efficient bioreduction of ezetimibe intermediate

Abstract: Ezetimibe is a selective acyl-coenzyme A: cholesterol acyltransferase (ACAT) inhibitor used in hypercholesterolemia. Synthesis of ezetimibe requires enantiopure 3-[5-(4-fluorophenyl)-5(S)-hydroxypentanoyl]-4(S)-4-phenyl-1,3-oxazolidin-2-one (FOP alcohol) as a crucial intermediate which is produced by reduction of the corresponding prochiral ketone (FOP dione). A new biocatalyst from acclimatized soil was screened for bioreduction of the above prochiral ketone. The microorganism was identified by 16S mRNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
6
1
Order By: Relevance
“…Although the lack of reduction of 1h is contradictory to a previous report (12), these results are in line with other reports (13,14). It is well known that amino and hydroxyl groups play a significant role in the activity of the catalyst.…”
Section: Resultscontrasting
confidence: 56%
“…Although the lack of reduction of 1h is contradictory to a previous report (12), these results are in line with other reports (13,14). It is well known that amino and hydroxyl groups play a significant role in the activity of the catalyst.…”
Section: Resultscontrasting
confidence: 56%
“…Further experiments with a different Paraburkholderia strain demonstrated that AP can be reduced by a carbonyl reductase (Singh et al 2009 ), which might serve as an evidence for further metabolization inside the cells. It is also known that Burkholderia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Two kinds of p -hydroxybenzoic acid esters, methyl paraben and propyl paraben, are degraded by B. latens (Amin et al 2010 ). Ezetimibe, a selective inhibitor of acyl-coenzyme A, was produced from reduction of 1-(4-fluorophenyl)-5-(2-oxo-4-phenyl-oxazolidin-3-yl)-pentane-1,5-dione in culture medium with B. cenocepacia (Singh et al 2009 ). It was thus anticipated that Burkholderia sp.…”
Section: Resultsmentioning
confidence: 99%